Elastic energy within the human plantar aponeurosis contributes to arch shortening during the push-off phase of running - Wager, J. C.; Challis, J. H. (Journal of Biomechanics, 2016)
During locomotion, the lower limb tendons undergo stretch and recoil, functioning like springs that recycle energy with each step. Cadaveric testing has demonstrated that the arch of the foot operates in this capacity during simple loading, yet it remains unclear whether this function exists during locomotion. In this study, one of the arch?s passive elastic tissues (the plantar aponeurosis; PA) was investigated to glean insights about it and the entire arch of the foot during running. Subject specific computer models of the foot were driven using the kinematics of eight subjects running at 3.1 m/s using two initial contact patterns (rearfoot and non-rearfoot). These models were used to estimate PA strain, force, and elastic energy storage during the stance phase. To examine the release of stored energy, the foot joint moments, powers, and work created by the PA were computed. Mean elastic energy stored in the PA was 3.1±1.6 J, which was comparable to in situ testing values. Changes to the initial contact pattern did not change elastic energy storage or late stance PA function, but did alter PA pre-tensioning and function during early stance. In both initial contact patterns conditions, the PA power was positive during late stance, which reveals that the release of the stored elastic energy assists with shortening of the arch during push-off. As the PA is just one of the arch's passive elastic tissues, the entire arch may store additional energy and impact the metabolic cost of running.